Polymorphic variations in the FANCA gene in high‐risk non‐BRCA1/2 breast cancer individuals from the French Canadian population. Issue 1 (11th September 2012) - Litim, Nadhir; Labrie, Yvan; Desjardins, Sylvie; Ouellette, Geneviève; Plourde, Karine; Belleau, Pascal; Durocher, Francine
Abstract : The majority of genes associated with breast cancer susceptibility, including BRCA1 and BRCA2 genes, are involved in DNA repair mechanisms. Moreover, among the genes recently associated with an increased susceptibility to breast cancer, four are Fanconi Anemia (FA) genes: FANCD1/BRCA2, FANCJ/BACH1/BRIP1, FANCN/PALB2 and FANCO/RAD51C. FANCA is implicated in DNA repair and has been shown to interact directly with BRCA1. It has been proposed that the formation of FANCA/G (dependent upon the phosphorylation of FANCA) and FANCB/L sub‐complexes altogether with FANCM, represent the initial step for DNA repair activation and subsequent formation of other sub‐complexes leading to ubiquitination of FANCD2 and FANCI. As only approximately 25% of inherited breast cancers are attributable to BRCA1/2 mutations, FANCA therefore becomes an attractive candidate for breast cancer susceptibility. We thus analyzed FANCA gene in 97 high‐risk French Canadian non‐BRCA1/2 breast cancer individuals by direct sequencing as well as in 95 healthy control individuals from the same population. Among a total of 85 sequence variants found in either or both series, 28 are coding variants and 19 of them are missense variations leading to amino acid change. Three of the amino acid changes, namely Thr561Met, Cys625Ser and particularly Ser1088Phe, which has been previously reported to be associated with FA, are predicted to be damaging by the SIFT and PolyPhen softwares. cDNA amplification revealed significant expression of 4 alternative splicing events (insertion of an intronic portion of intron 10, and the skipping of exons 11, 30 and 31). In silico analyzes of relevant genomic variants have been performed in order to identify potential variations involved in the expression of these spliced transcripts. Sequence variants in FANCA could therefore be potential spoilers of the Fanconi‐BRCA pathway and as a result, they could in turn have an impact in non‐BRCA1/2 breast cancer families.